2023
DOI: 10.3390/biomedicines11102651
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Modulates M-Type K+ and Hyperpolarization-Activated Cation Currents

Yen-Chin Liu,
Edmund Cheung So,
Sheng-Nan Wu

Abstract: Cannabidiol (CBD) is a naturally occurring compound found in the Cannabis plant that is known for its potential therapeutic effects. However, its impact on membrane ionic currents remains a topic of debate. This study aimed to investigate how CBD modifies various types of ionic currents in pituitary GH3 cells. Results showed that exposure to CBD led to a concentration-dependent decrease in M-type K+ currents (IK(M)), with an IC50 of 3.6 μM, and caused the quasi-steady-state activation curve of the current to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Controversially, CBD inhibits the M-type current in GH3 tumor cells but activates the same current in rat hippocampal neurons. 22,33 The difference may reflect distinct channel isoforms expressed in each cell type. In HEK cells, CBD directly activates the heteromeric Kv7.2/7.3 channel.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Controversially, CBD inhibits the M-type current in GH3 tumor cells but activates the same current in rat hippocampal neurons. 22,33 The difference may reflect distinct channel isoforms expressed in each cell type. In HEK cells, CBD directly activates the heteromeric Kv7.2/7.3 channel.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Among KCNQ genes, KCNQ2 and KCNQ3 subunits heteromultimerize to form the channels responsible for I K(M) in neurons [37]. In recent research conducted on pituitary GH 3 cells, it was demonstrated that exposure to CBD leads to the suppression in the amplitudes of I K(M) and the hyperpolarization-activated cation current (I h ), with the corresponding IC 50 values of 3.6 and 3.3 µM, respectively [14]. The biophysical property of I h is distinctive, marked by its slow activation kinetics during sustained hyperpolarization [38,39].…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%